(3Odjd Yedj deSjQj GdehGQO GdHTQjI aj GdhXjaI GdYehejI hab GdJTQjY GdLRGFQjs - (3eMeO(B, (3HdHQjcs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2019)
(3jMJhj gPG GdcJGH Ydi JGQjN JSjjQ GdehGQO GdHTQjI, JMdjd GdhXGFa, JNWjW GdehGQO GdHTQjI, GdJhXja(B- (3GSJbWGH hGNJjGQ GdehGQO GdHTQjI(B-(3, Jbjje GdehGQO GdHTQjI, JSjjQ GdeSGQ Gdegfj ddehXajf, JSjjQ GdCLhQ hGdQhGJH hGdJYhjVGJ, GdJchjf hGdJOQjH, GdOhGaY hJSjjQ fXGe GdMhGaR, GdfbGHI, fXGe eTGQcI GdYeGd hGdehXajf aj JSjjQ GdeDSSGJ GdeSJNOeI hab GdJTQjY GdLRGFQj, GdfRGYGJ GdaQOjI hGdLeGYjI, GdeQGLYI GdGLJeGYjI, CNdGbjGJ GdegfI, GdhVYjGJ GdbGfhfjI ddehXa hMQcGJ fbdg aj GdhXjaI GdYehejI, GdfXGe GdJCOjHj ddehXa hCNjQG fXGe GdJbGYO hab GdJTQjY GdLRGFQj(B.s
(3eQGLY U(B.177s
Keywords: (3EOGQI GdCaQGOs; (3EOGQI GdehGQO GdHTQjIs; (3GdbWGY GdYGe(B- (3bhGfjf hJTQjYGJs